Perilaku Kepemimpinan Lintas Budaya Dimensi LDBQ XII Pada Kepuasan Kerja Praktisi Perbankan Di Jawa Tengah - Asri Laksmi Riani; Dodi Wirawan Irawanto; Yanki Hartijasti; Ulfa Puspita (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2022)
This study identifies the determinants of leadership behavior using LBDQ XII and job satisfaction with a sample of bank staff and managers in the island of Central Java. The leadership style in a country is characterized by cross-cultural as a form of national culture that plays an important role in the application of the leadership theory in a country. The role of leadership on the job satisfaction of supervisors and managers is very important to know to see their performance, which will result in organizational performance. The data collection in this study was conducted by distributing online questionnaires to 60 entrepreneurs in the banking sector. LBDQ XII containing 100 instruments and job satisfaction using the Minnesota Satisfaction Questionnaire (MSQ) containing 20 items in the study population. The results show that Indonesian banking practitioners, especially in Central Java, have leaders who are persuasive, production emphasis, predictive accuracy, tolerance for freedom and initiative for structure have the most role in the job satisfaction of banking supervisors and managers in Central Java, respectively Java.